HUBUNGAN TONSILITIS KRONIS DENGAN KEJADIAN OTITIS MEDIA AKUT PADA ANAK USIA 1-17 TAHUN DI POLIKLINIK THT RUMAH SAKIT BUDI KEMULIAAN TAHUN 2019 -2021 - Miralza Diza; Dahlan Gunawan; Loviga Ferbina Putri Sirait (Universitas Batam, 2023)
Background: Chronic tonsilitis (CT) is a swelling or inflammation of the palatine tonsils which is particularly severe as a result of not receiving inadequate medical treatment. AOM as the result of CT happens due to hypertrophy of the tonsils causing an obstruction in the Eustachian tube. Methods: This study employs an analytic observational approach with cross sectional design which took place at the ENT (Ear-Nose-Throat) Polyclinic of Budi Kemuliaan Hospital.The population of the research was the entire number of patients visiting the polyclinic between the period of 2019-2021. The data collecting technique employs simple random sampling by using the patients’ medical history as the instrument.The data analysis technique employs Chi-square. Results: The Chi-square analysis further proved no significant effect on the hypothesis of correlation between chronic tonsilitis (CT) and the incidence of acute otitis media (AOM) where p-value was 0.171 (>0.05). Conclusion: From the result, this study confirms no confidence on the significance of correlation between chronic tonsilitis (CT) and the incidence of acute otitis media (AOM) in patients aged 1-17 years at the ENT Polyclinic of Budi Kemuliaan Hospital in 2019-2021.